Effects of Meteorological and Fuel Variables on Fire Behavior in Agricultural Burning - Ramos Rodríguez, Marcos Pedro (2025)
Fire behavior depends on meteorological variables, fuel characteristics, and topography. This study aimed to analyze the effects of meteorological and fuel variables on fire behavior during agricultural burning in Membrillal parish, Jipijapa, Manabí, Ecuador. The research followed a non-experimental, cross-sectional design. Fifteen plots (5 × 1.5 m) were established on fuel rows composed of Zea mays L. residues and weeds. Five plots were burned during each work session (morning, midday, and afternoon). Meteorological, fuel, and fire behavior variables were measured, and average values were obtained for each session. Although the experimental burns were conducted in early August (early burning period), complete combustion of the fuel was achieved. The high coefficient of determination found in the regression analysis between the dry weight of the fuel and the heat released per unit area suggests that the resulting equation could be used to adjust the burning pattern by reducing fuel weight per m²—achievable by increasing the width of fuel rows.